Self-reported antidepressant use among depressed, low-income homebound older adults: class, type, correlates, and perceived effectiveness - Choi, Namkee G (Blackwell Publishing Inc, 2012)
Little research has been done on the use of antidepressants among homebound older adults, especially low-income homebound older adults, and their perceptions of the effectiveness of their medication. The purposes of this study were to examine self-reported use of antidepressants among depressed homebound older adults, class and type of antidepressants used, individual-level correlates of antidepressant use, and users’ perceptions of the effectiveness of antidepressants. Data on self-reported use of antidepressants were obtained as part of a feasibility study of short-term telehealth problem-solving therapy for depressed low-income homebound adults (n = 162) aged 50 or older. The 24-item Hamilton Rating Scale for Depression (HAMD) was used to assess depression severity. The findings show that about half of the study participants were taking antidepressants, with 26.6% of those on antidepressants rating their medications very effective and 21.5% rating them effective. Female gender was positively, but older age and being Black/African American were negatively associated with the likelihood of antidepressant use. Perceived effectiveness of antidepressants was negatively associated with older age and the HAMD score. The findings suggest that personalized approaches to depression management may be needed in subgroups of depressed older adults, including culturally tailored medication counseling in Black/African-American older adults.